FINANCIAL MARKETS AND BONDS: AN IN-DEPTH ANALYSIS - Firdavs Kazakov Farhod ugli (PT ANTIS International Publisher, 2024)
This comprehensive article provides a detailed analysis of financial markets and bonds, focusing on the structure of financial markets, the characteristics, types, and valuation methods of bonds, their significance in the global economy, and the associated risks. The article distinguishes between money markets and capital markets, highlighting the various instruments traded within each. It delves into different types of bonds, explaining their unique features and uses. Additionally, it discusses the importance of bonds in funding, portfolio diversification, income generation, economic indicators, and risk management. Finally, the article outlines the key risks associated with bond investments, emphasizing the need for informed decision-making in this area